OPTIMISASI KEUNTUNGAN PRODUKSI NUGGET BEKU MENGGUNAKAN PROGRAM LINIER - Rina Filia Sari; Afnaria Afnaria; Syech Suhaimi; Hani Maulida Hasibuan (Universitas Islam Sumatera Utara, 2025)
This study aims to determine an optimal production strategy to maximize profit at “Umar Frozen Food” in Hasahatan Julu Village. The research focuses on two types of chicken nuggets: long and flat shapes, considering limited raw materials and production time. The research method applied is linear programming using the simplex method. Data were collected through observation, interviews, and documentation of the production process. The results indicate that the maximum daily profit of Rp10.640,00 is achieved by producing only 2.8 units of flat chicken nuggets and none of the long type. In conclusion, the simplex method effectively aids small businesses in making efficient production decisions and maximizing profit under resource constraints.